Great Gatsby and the Global South : intergenerational mobility, income inequality, and development - Sakri, Diding; Sumner, Andrew, 1973-; Yusuf, Arief Anshory (Cambridge elements, 2023)
In the Global South economic mobility across generations or intergenerational economic mobility is in and of itself an important topic for research with consequences for policy. This 'Element' surveys the area, conceptually and empirically.